2017
DOI: 10.1007/s10067-017-3636-3
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of biologic utilization patterns in patients with psoriatic arthritis

Abstract: The aim of the study is to examine the frequency and costs associated with above-label dosing of biologics in patients with psoriatic arthritis (PsA). MarketScan identified adults with ≥1 International Classification of Diseases, Clinical Modification diagnosis for PsA and ≥1 pharmacy claim for biologics of interest between January 1, 2011 and December 31, 2013. The first biologic claim was the index date with a 1-year follow-up period and three additional months to confirm continuous biologic use. Exclusion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
2
8
1
Order By: Relevance
“…Patients treated with apremilast have lower pharmacy costs in addition to lower outpatient medical costs and lower total healthcare costs, suggesting that savings may be related to reductions in expenditures for outpatient care or laboratory fees to monitor or treat adverse events that have been associated with biologics. Comparison to previous administrative-based claims analyses of patients with PsA is challenging due to differences in study methodology; however, our 1-year total direct cost results for PsA patients treated with biologics were consistent with previous publications that evaluated the total costs and total pharmacy costs for PsA patients treated with biologics [23,24]. Our 1-year total pharmacy cost estimates were slightly lower than one previous study that included apremilast and estimated the 1-year pharmacy costs per responding patient to be $53,704 for apremilast, $56,273 for adalimumab and $65,750 for etanercept (2014 US dollars) [25].…”
Section: Discussionsupporting
confidence: 88%
“…Patients treated with apremilast have lower pharmacy costs in addition to lower outpatient medical costs and lower total healthcare costs, suggesting that savings may be related to reductions in expenditures for outpatient care or laboratory fees to monitor or treat adverse events that have been associated with biologics. Comparison to previous administrative-based claims analyses of patients with PsA is challenging due to differences in study methodology; however, our 1-year total direct cost results for PsA patients treated with biologics were consistent with previous publications that evaluated the total costs and total pharmacy costs for PsA patients treated with biologics [23,24]. Our 1-year total pharmacy cost estimates were slightly lower than one previous study that included apremilast and estimated the 1-year pharmacy costs per responding patient to be $53,704 for apremilast, $56,273 for adalimumab and $65,750 for etanercept (2014 US dollars) [25].…”
Section: Discussionsupporting
confidence: 88%
“…Unlike previous real-world studies that have shown shorter persistence with subsequent lines of biologic therapy in patients with PsA, in our study discontinuation rates and time to discontinuation were similar between biologic-naive and -experienced patients (43.4 and 44.3%, respectively), but additional adjusted analyses are needed to better understand factors associated with persistence [33,40]. The mean PDC with adalimumab (0.65), certolizumab pegol (0.49), etanercept (0.60) and golimumab (0.59) in our study was slightly lower than those previously reported among patients with PsA from the same database at 12-months of follow-up (mean PDC = 0.8 for adalimumab, etanercept and golimumab) [41], and comparable to analysis of another administrative claims database (adalimumab [0.56], certolizumab pegol [0.51], etanercept [0.57] and golimumab [0.61]) [34]. The overall proportion of patients adherent (PDC ≥0.8) to their index therapy is also similar to what was previously observed during the first year of therapy in patients with PsA, ankylosing spondylitis or rheumatoid arthritis who initiated an sc.…”
Section: Discussioncontrasting
confidence: 74%
“…Our findings are also consistent with a study of real-world costs among biologic-naive PsA patients conducted by Feldman et al, which showed that apremilast initiators had lower healthcare costs compared with patients treated with biologics, primarily due to lower outpatient pharmacy costs [15]. The higher pharmacy costs observed with biologics in our study may also be due to off-label dosing; in a study of anti-TNF therapy for PsA by Schwartzman et al, off-label dosing was associated with significantly higher healthcare costs [22].…”
Section: Discussionsupporting
confidence: 43%